CLINICAL OUTCOME OF STROKE PATIENTS BASED ON THE NATIONAL INSTITUTES OF HEALTH STROKE SCALE (NIHSS) IN A TERTIARY HOSPITAL - Liunardo Bintang Pratama; Lisda Amalia; Cep Juli; Uni Gamayani; Asep Nugraha Hermawan (Malang Neurology Journal, 2022)
Background: Stroke is the second leading cause of death and the third cause of disability globally. Clinical outcomes caused by stroke are varied and influenced by various factors.